Exploring Atypical Fluorine–Hydrogen Bonds and Their Effects on Nucleoside Conformations. Issue 61 (9th October 2018) - O'Reilly, Daniel; Stein, Robin S.; Patrascu, Mihai Burai; Jana, Sunit Kumar; Kurian, Jerry; Moitessier, Nicolas; Damha, Masad J.
Abstract: The ability of fluorine to serve as a hydrogen‐bond acceptor has been debated for many years. Short fluorine–hydrogen contacts are thought to play a key role in stabilizing some complex supramolecular systems. To directly probe the existence of fluorine–hydrogen bonds, we have performed NMR spectroscopy and computational modeling on a series of C2′‐fluorinated nucleosides. Specifically, quantum mechanics/molecular mechanics (QM/MM) analysis and [ 19 F, 1 H] HMBC NMR experiments provided direct evidence for a C−H⋅⋅⋅F hydrogen bond in a 2′‐F, 4′‐C‐α‐alkyl‐ribonucleoside analogue. This interaction was also supported by QTAIM and NBO analyses, which confirmed a bond critical point for the C−H⋅⋅⋅F interaction (0.74 kcal mol −1 ). In contrast, although conformational analysis and NMR experiments of 2′‐deoxy‐2′‐fluoro‐arabinonucleosides indicated a close proximity between the 2′‐fluorine and the H6/8 protons of the nucleobase, molecular simulations did not provide evidence for a C−H⋅⋅⋅F hydrogen bond. Abstract : Detecting the atypical : Direct evidence for δ+ C−H⋅⋅⋅F δ− bonds that play a subtle but important role in conformational stability (see picture).